Does Digital Finance Promote Business Performance of Manufacturing? - Xu, Xiyue (Transactions on Economics, Business and Management Research, 2024)
Manufacturing is the lifeblood of China's economy, and digital finance (DF), with its broad applicability, significantly aids in improving the business performance of manufacturing industry (BPMI). Utilizing panel data from China's 30 provinces over the decade from 2011 to 2021, this paper employs a fixed-effect model to analyze the influence of DF on the BPMI. Additionally, it introduces a mediation model and a threshold model to uncover the underlying mechanisms through which DF impacts the BPMI. This paper uncovers that DF significantly bolsters the business performance of the manufacturing industry, primarily by fostering innovation. Moreover, it reveals that industrialization's level exerts a non-linear threshold impact on the capacity of DF to enhance BMPI. These insights are instrumental for proactively shaping a novel framework for the convergence of digital finance and the manufacturing industry, thereby contributing to the enhancement of BMPI.